One-Dimensional Multi-Channel Photonic Crystal Resonators Based on Silicon-On-Insulator With High Quality Factor - Faneca, Joaquin; Perova, Tatiana S.; Tolmachev, Vladimir; Baldycheva, Anna (Frontiers in Physics, 2018)
We have theoretically and experimentally demonstrated a Fabry-Pérot (FP) resonators based on a Si-air one-dimensional photonic crystal (1D PhC) with coupled triple-cavity modes (or defects). These defects are obtained by filling selected air channels in the 1D PhC with an actively reconfigurable fluid. Simulations of the optical properties of these FP resonators were performed in the wide infrared spectral range. It is shown that by changing the refractive index, nc, of the fluid simultaneously in all three channels, a set of narrow triple resonance peaks can be obtained within wide stop-bands of different order in the infrared range. In addition, at certain values of nc, splitting of the triple resonance peaks into a doublet and a single peak with a significantly larger quality factor, Q=21200, occurs. Prototype devices based on Silicon-On-Insulator platform were fabricated and characterized by electro-optical and spectroscopic measurements. The electro-optical measurements demonstrate the possibility of refractive index manipulation of the filler in the FP channels individually or simultaneously. Spectroscopic measurements performed in the range 1540 – 1630 nm using fibre-coupling confirm the presence of triple resonance peaks in the 3rd stop-band in the absence of an electric field applied to the FP channels. At an applied voltage of 10 V to the middle channel, an increase of Q to 3720 in the single peak is registered which is the highest Q demonstrated in SOI based 1D PhC to date.